국내 유통 건조 농산물의 식품첨가물 및 유해 중금속 위해성 평가 - 김도우; 김효희; 임소영; 최수연; 조은혜; 정진; 이세미; 강인숙; 김애경; Do-Woo Gim; Hyo-Hee Kim; So-Young Lim; et al. (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2025)
Sixty dried agricultural products were collected from February to July 2024. Among these, 16 samples were randomly purchased from large supermarkets and local markets in Gwangju, and 44 were obtained from online marketplaces. Only products labeled with phrases such as “No Food Additives” or “100% Raw Ingredients” were selected for analysis. The aims of this study were to determine the concentrations of sulfur dioxide, preservatives, artificial colorants, and toxic heavy metals (lead and cadmium) in dried agricultural products, assess their risk indices, and provide foundational data to establish relevant regulatory standards. The results revealed that sulfite compounds were detected in some samples, with the highest sulfur dioxide concentrations found in gourds (82.99- 1046.95 mg/kg), apricots (10.87-529.45 mg/kg), and konjac powder (23.59-475.92 mg/kg). The highest sulfur dioxide risk index was observed in persimmons, with values ranging from 4.74% to 16.61% for male and 6.26% to 26.84% for female consumers. Sweet potatoes followed, with risk index values of 6.87% and 11.29% for male and female consumers, respectively. All the samples exhibited sulfur dioxide risk indexes below 100%, indicating safety. No preservatives or artificial colorants were detected in any of the samples, suggesting that sulfites can be used as alternatives to preservatives in certain products. The concentrations of lead in dates (9.55-137.09 μg/kg) and gourds (10.76-49.14 μg/kg) and cadmium in gourds (16.36-51.76 μg/kg) were within safe limits, with risk indexes below 100%. This study provides crucial baseline data for evaluating the safety of dried agricultural products. Furthermore, it underscores the need for more comprehensive risk assessments that consider the interactions between sulfur dioxide, heavy metals, and consumption patterns. Lastly, it highlights the necessity of strengthening regulatory standards to better protect consumers.